Pengaruh Digital Marketing dan Kualitas Produk Terhadap Minat Beli Konsumen Produk Makanan Pada UMKM Kota Bima - Ayu Puryanti; Sri Ernawati; Julaiha Julaiha (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to analyze the influence of digital marketing and product quality on consumer buying interest in food products produced by MSMEs in Bima City. The research method used is quantitative with a survey approach. Data was collected through a questionnaire distributed to 200 respondents who are consumers of food products from MSMEs in Bima City. Data analysis was carried out using multiple linear regression to determine the influence of independent variables (digital marketing and product quality) on dependent variables (consumer buying interest). The results of the study show that both digital marketing and product quality have a positive and significant influence on consumer buying interest. These findings indicate that efforts to improve product quality and the implementation of effective digital marketing strategies can increase consumer buying interest, thus having a positive impact on MSME sales in Bima City.